2019
DOI: 10.1002/ajoc.201900469
|View full text |Cite
|
Sign up to set email alerts
|

Manganese‐Catalyzed Oxime‐Directed ortho‐C−H Amidation in Ionic Liquids

Abstract: We have developed an efficient amidation of aromatic oximes via CÀ H bond activation using readily available sulfonyl azides as amidation reagents. This reaction is catalyzed by a base metal catalyst system -MnBr(CO) 5 /[Hmim]OTf. Our method offers excellent chemical yields and regioselectivity with good functional group tolerance. The reusability of MnBr(CO) 5 /[Hmim]OTf system makes it relatively practical for large scale CÀ H amidations.[a] X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Meanwhile, Xu et al realized the manganese-catalyzed C-H amidation of arenes with sulfonyl azides as amination reagents (Scheme 5g). 31,32 At the same year, Wang et al and Ruan et al reported the manganese-catalyzed C-H addition of heteroarenes to ketenimines (Scheme 5h). 33,34 When estergroup substituted ketenimines were utilized, 2-enaminylated indole products were obtained.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Meanwhile, Xu et al realized the manganese-catalyzed C-H amidation of arenes with sulfonyl azides as amination reagents (Scheme 5g). 31,32 At the same year, Wang et al and Ruan et al reported the manganese-catalyzed C-H addition of heteroarenes to ketenimines (Scheme 5h). 33,34 When estergroup substituted ketenimines were utilized, 2-enaminylated indole products were obtained.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The next year, the same authors applied their manganese catalyst for the sulfonamidation of a diverse range of aromatic oximes 63 with sulfonyl azides 64 by using imidazolium ionic liquid [Hmim]OTf as the solvent (Scheme 21). 62 This time, no additive was used and the couplings were performed under relatively milder conditions. Importantly, MnBr(CO) 5 /[Hmim] OTf system could be easily separated from the nal reaction mixture and reused for at least ve times with tangible decrease in its catalytic activity.…”
Section: Manganese-catalyzed Reactionsmentioning
confidence: 99%
“…Among these wellconstructed routes, transition metal-catalyzed C−H amidation is an efficient, direct, and classic method to access C−N bonds. 6−12 Many transition metals, such as Mn, 13,14 Fe, 15,16 Co, 17−19 Ni, 20,21 Cu, 22,23 Ru, 24−26 Rh, 27−29 Pd, 30,31 and Ir, 8,32−51 have been employed in the C−H amidation.…”
Section: Introductionmentioning
confidence: 99%
“…The carbon–nitrogen bonds are present in many of the most privileged structures found in both natural products and synthetic bioactive molecules, which play a pivotal role in medicinal chemistry, pharmaceutical science, and functional materials. Hence, the approaches to create the C–N bonds have been studied in the past decades. Among these well-constructed routes, transition metal-catalyzed C–H amidation is an efficient, direct, and classic method to access C–N bonds. Many transition metals, such as Mn, , Fe, , Co, Ni, , Cu, , Ru, Rh, Pd, , and Ir, , have been employed in the C–H amidation.…”
Section: Introductionmentioning
confidence: 99%